2018
DOI: 10.1016/j.energy.2018.08.029
|View full text |Cite
|
Sign up to set email alerts
|

Energy, exergy and advanced exergy analysis of a milk processing factory

Abstract: Abstract:Energy, exergy and advanced exergy methods are used in this study to analyse a milk processing facility which is one of the largest energy consumers within the food industry in Denmark. While a conventional energy analysis maps the energy flows of the system and suggests opportunities for process integration, an exergy analysis pinpoints the locations, causes and magnitudes of thermodynamic losses. The advanced exergy analysis further identifies the real potential for thermodynamic improvements of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(37 citation statements)
references
References 37 publications
0
37
0
Order By: Relevance
“…[36][37][38] The pinch method uses data for heating and cooling demands of the process streams and an assumed minimum temperature difference ΔT min for heat exchange to determine the maximum internal heat recovery and minimum utility demands of the process. Bühler et al 39 used a case study to compare pinch analysis with different forms of exergy analysis and concluded that although more process improvement possibilities could be identified with the exergy-based methods, only some of these were possible to implement in practice. Furthermore, pinch analysis was regarded as relatively easy, and more importantly, as the easiest analysis method to communicate to nonscientific staff.…”
Section: Pinch-based Methods For Targeting Of Industrial Excess Heatmentioning
confidence: 99%
“…[36][37][38] The pinch method uses data for heating and cooling demands of the process streams and an assumed minimum temperature difference ΔT min for heat exchange to determine the maximum internal heat recovery and minimum utility demands of the process. Bühler et al 39 used a case study to compare pinch analysis with different forms of exergy analysis and concluded that although more process improvement possibilities could be identified with the exergy-based methods, only some of these were possible to implement in practice. Furthermore, pinch analysis was regarded as relatively easy, and more importantly, as the easiest analysis method to communicate to nonscientific staff.…”
Section: Pinch-based Methods For Targeting Of Industrial Excess Heatmentioning
confidence: 99%
“…Energy and exergy analyses are widely used methods for the investigation of processes [36,37], power plants [38][39][40], industrial plants [41,42] or their components. [43,44].…”
Section: Energy and Exergy Analysesmentioning
confidence: 99%
“…From the second law of thermodynamics, the definition of exergy analysis can be derived [33]. The main exergy balance equation according to [24] and [34] can be defined as:…”
Section: Energy and Exergy Analysis Of Any Control Volumementioning
confidence: 99%